Adsorption Power of Palm Shell Activated Carbon (Elaeis Guineensis) in the Filtration Process of Water Treatment: Daya Serap Karbon Aktif Cangkang Kelapa Sawit (Elaeis Guineensis) Pada Proses Filtrasi Pengolahan Air - Mawardi, Rifqi; Hermansyah Fahnur; M. Ilham Nurdin; Setyo Erna Widiyanti (Jurnal Agritechno, 2024)
The impact of water pollution can lead to ecological imbalances and act as carriers of infectious diseases. Therefore, water purification is necessary before it is used to improve water quality. One method for water purification is using activated carbon from palm oil shells (Elaeis guineensis). This study aims to determine the optimal flow rate for reducing Total Suspended Solids (TSS) and Lead (Pb) in the water filtration process. The research includes the processes of carbonization, activation, filtration, and testing. The carbonization method involves burning in a drum at approximately 350°C for about 2 hours. The palm oil shells are activated with 3M H3PO4. The filtration stage uses 30 grams of activated carbon with flow rate variations of 30, 40, 60, 80, and 100 mL/hour. Filtration is conducted for 1 hour with sampling every 10 minutes. The results show that a flow rate of 40 mL/min is optimal for reducing TSS, while a flow rate of 30 mL/min is optimal for reducing Pb.